2019
DOI: 10.1093/icesjms/fsz045
|View full text |Cite
|
Sign up to set email alerts
|

Individual trophic specialization in juvenile European seabass: implications for the management of a commercially important species

Abstract: Individual differences in diet can play an important role defining a population's ecological niche and its role within food webs and habitats, but individual trophic specialization is rarely considered in a fisheries context. Stocks of European seabass, Dicentrarchus labrax, have declined in recent years, and policy has focused on managing fishing effort. Inshore nursery grounds represent a critical habitat in terms of recruitment to standing stocks, and improved understanding of the ecology of juvenile seabas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…However, contrary to our expectation, the highest individual specialisation in the M. forestii diet was found in stands with low macrophyte biomass. This seems likely to be related to the increased intraspecific competition intensified by the lower resource availability that is probably found in less complex habitats (Araújo et al, 2010;Cobain et al, 2019;Kovalenko et al, 2012). During the dry season, when we carried out the sampling, intraspecific competition tends to intensify since resource availability is lower due to the contraction of ecosystems (Correa & Winemiller, 2014;Costa-Pereira, Tavares, Camargo, & Araújo, 2017;Fitzgerald, Winemiller, Sabaj Pérez, & Sousa, 2016;Gomes, Bulla, Agostinho, Vasconcelos, & Miranda, 2012).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, contrary to our expectation, the highest individual specialisation in the M. forestii diet was found in stands with low macrophyte biomass. This seems likely to be related to the increased intraspecific competition intensified by the lower resource availability that is probably found in less complex habitats (Araújo et al, 2010;Cobain et al, 2019;Kovalenko et al, 2012). During the dry season, when we carried out the sampling, intraspecific competition tends to intensify since resource availability is lower due to the contraction of ecosystems (Correa & Winemiller, 2014;Costa-Pereira, Tavares, Camargo, & Araújo, 2017;Fitzgerald, Winemiller, Sabaj Pérez, & Sousa, 2016;Gomes, Bulla, Agostinho, Vasconcelos, & Miranda, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…ecomorphological diversity, individual specialisation, macrophyte biomass, Moenkhausia forestii, nested diets niche variation hypothesis (Niche Hypothesis Variation), which suggests that niche expansion may occur due to variation in resource use among individuals of a single population. Thus, species considered generalists may be composed of specialist individuals that use a small subset of the entire niche of the population (Bolnick et al, 2003;Cobain, Steward, Trueman, & Jensen, 2019;Cunha, Wolff, & Hahn, 2018;Latli, Michel, Lepoint, & Kestemont, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This could be caused by additional physiological stress due to a greater difference in marine temperatures and riverine temperatures (Jutila et al, 2005). Another extrinsic variable with a relatively large effect size was sea bass abundance, a species known to predate on S. salar smolts (Riley et al, 2011), and that can be dietary specialists at an individual level, despite being generalists at population levels (Cobain et al, 2019). Riley et al (2011) found that sea bass stomach contents from the tidal River Frome included salmonid smolts, though whether the prey were S. salar or Salmo trutta was difficult to determine.…”
Section: Discussionmentioning
confidence: 99%
“…If resources are distributed more evenly in space, then competitive interactions are less likely than when they are aggregated, but the likelihood of inter‐ and intra‐species competition increases as resource distributions become more heterogeneous (Ward et al ., 2006), as is typical in coastal environments (Le Pape & Bonhommeau, 2015). Diet studies conducted in coastal and estuarine areas are generally focused on single species ( e.g ., Cobain et al ., 2019) or on several species but in a single location ( e.g ., Cabral et al ., 2002; Carter et al ., 1991). Although such studies provide useful insights into resource partitioning, they do not fully capture the spatial and temporal heterogeneity of consumed prey in these often densely populated and dynamic regions (Buchheister & Latour, 2010; Mariani et al ., 2011), and therefore the degree of consistency in observed dietary behaviours is poorly understood.…”
Section: Introductionmentioning
confidence: 99%